Empowering English Students: SEM Analysis of Motivation and Academic Outcomes in Al-Islam Muhammadiyah Course - Desri Arwen; Euis Yanah Mulyanah; Ishak Ishak; Yayat Ruhiat; Yujin Lee (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the complex relationships among Educational Psychology (EP), Al-Islam Muhammadiyah Course (AMC), English Language Education Students (ELES), Learning Motivation (LM), and Academic Outcomes (AO) in a value-based educational context. Understanding these interactions can inform curriculum design and instructional strategies to enhance student achievement. A quantitative approach was employed using an explanatory survey method. Data were collected from 165 ELES enrolled in AMC courses. Structural Equation Modeling (SEM) with LISREL software was utilized to examine direct and indirect effects among variables. Instrument validity and reliability were assessed through Confirmatory Factor Analysis (CFA), with Composite Reliability (CR 0.7) and Average Variance Extracted (AVE 0.5) ensuring robust psychometric properties. Findings indicate that EP and AMC have minimal direct effects on LM and AO; however, their influence is significantly mediated through LM. In contrast, ELES exhibits a direct, positive impact on AO, highlighting its role in fostering essential academic competencies. Despite an elevated RMSEA value (0.144), the model remains theoretically sound and interpretable. The study confirms that LM serves as a crucial mediator, reinforcing established theoretical frameworks on student motivation and achievement. Institutions can leverage these insights by incorporating motivation-driven teaching strategies within the ELES curriculum. This research underscores the importance of LM in enhancing AO. While statistical model fit is essential, theoretical coherence remains paramount in evaluating educational models. Future studies should further explore motivational interventions to optimize student learning outcomes.